The Architecture of Protoliterate Period: Arsitektur Periode Protoliterasi - Al-Yasiri, Farah Shaker (Indonesian Journal on Health Science and Medicine, 2024)
Mesopotamian architecture was characterized by a number of important elements created by ancient builders in line with the nature of the region, the layout and formations of buildings, as well as their association with the types of structural materials used in the construction process. The achievements of the ancient Iraqis in architecture were many, and among their innovations was their high ability to innovate elements from early times based on the results of archaeological excavations. One of the things that draws attention in the architecture of this era is the magnitude of the buildings and the interest in the defensive fortifications represented by the walls, so they were very huge, reaching about two meters approximately, but in terms of aesthetics, this era was famous for a kind of decoration of facades and columns known among researchers for the decoration of beautiful mosaics, which has become a feature of this era. Highlights: Mesopotamian architecture emphasized massive structures and defensive fortifications. Innovations included decorative mosaics and aesthetic facade designs. Ancient builders adapted designs to regional materials and environment. Keywords: Mesopotamia; architecture; mosaic decoration; defensive fortifications; fences